Answer:
0
Step-by-step explanation:
(-4,0) and (3,2)
m1=(2-0)/(3+4)=2/7
y=2/7x+b1, using point (-4,0) to find b1 (substitute x=-4 and y=0 in the form)
0=2/7*(-4)+b1 ⇒ b1= 8/7
-----
(-3,2) and (4,0)
m2=(0-2)/(4+3)= -2/7
y= -2/7x+b2, using point (4,0) to find b2 (substitute x=4 and y=0 in the form)
0= -2/7*4+b2 ⇒ b2=8/7
----
m1b2+m2b1= 2/7*8/7 -2/7*8/7=0
9514 1404 393
Answer:
15. f(x) +g(x) = 7x +2
16. f(x) -g(x) = -3x +8
17. h(x) · g(x) = 35x -21
Step-by-step explanation:
Substitute the function definition for each function expression and simplify.
__
15. f(x) + g(x) = (2x +5) +(5x -3)
f(x) +g(x) = 7x +2
__
16. f(x) - g(x) = (2x +5) -(5x -3)
f(x) -g(x) = -3x +8
__
17. h(x) · g(x) = (7) · (5x -3)
h(x) · g(x) = 35x -21
Answer:
8/15
Step-by-step explanation:
When multiplying fractions, simply multiply the numbers straight across. First, multiply the numerators to get 8. Then, multiply the denominators and you'll get 15.
Answer: 8/4
Step-by-step explanation: if I’m wrong just watch the video for a hint it helps
Answer: use order of operstions
Step-by-step explanation: